Maraviglia: Rezeptionsgeschichte(n) von der Antike bis in die Moderne : Festschrift für Ingo Herklotz - Bell, Peter; Fehrmann, Antje; Müller, Rebecca; Olariu, Dominic (Studien zur Kunst, 2022)
Traces the history of reception from antiquity to the modern age and across genres, including art history, early Christian archaeology, cultural history, and the history of science and literature
Keywords: Herklotz, Ingo; Festschrift; Geschichte; Rezeptionsforschung; Kunstgeschichte; Geschichte 800 v. Chr.-1940; Rezeption; Kunst